PERSEPSI PENGGUNA TERHADAP TINGKAT KEPENTINGAN ELEMEN RUANG TERBUKA PUBLIK DI KOMPLEK ALUN-ALUN UTARA SURAKARTA - Ghufroni Arsyad; Ahmad Sarwadi (Jurnal Arsitektur ARCADE, 2019)
Abstract: This Study aims to understand the level of interest of public space element based on user perception who are categorized by visitor and traders in complex of north alun-alun surakarta. The study was conducted with a questionnaire of 100 visitors and 33 traders from the average population in the field divided into 4 segments to find out more in detail. Questionnaire data were analyzed with Multidimensional Scaling in SPSS to determine the ranking of the interests of 21 elements of public open space. Findings with double scaling according to visitors' perceptions that Pedestrian (Rank 1), Parking (rank 2) and Vegetation (Rank 3) while according to Pedestrian traders (rank 1), Places to Eat and drink (rank 2), Kiosk (Rank 3). In conclusion, the Pedestrian became the most important element in the public open space in Surakarta's northern plaza complex. The influence of the level of importance of elements of public open space varies depending on the settings and character of the open space itself.Keyword: Perception, Public Open Space, Multidimensionl ScalingAbstrak: Studi ini bertujuan untuk mengetahui tingkat kepentingan elemen ruang terbuka publik bedasarkan persepsi pengguna yang dikategorikan pengunjung dan pedagang di komplek alun-alun utara Surakarta. Studi dilakukan dengan kuisioner sejumlah 100 pengunjung dan 33 pedagang dari populasi rata-rata di lapangan yang di bagi 4 segmen untuk mengetahui lebih detail. Data kuisioner dianalisa dengan Multidimensional Scaling pada SPSS untuk mengetahui peringkat kepentingan dari 21 elemen ruang terbuka publik. Hasil Temuan dengan penskalaan ganda menurut persepsi pengunjung bahwa Pedestrian (Peringkat 1), Parkir (peringkat 2) dan Vegetasi (Peringkat3) sedangkan menurut pedagang Pedestrian (peringkat1), Tempat Makan/minum (peringkat2), Kios (Peringkat3). Kesimpulanya Pedestrian menjadi elemen yang paling penting di ruang terbuka publik di komplek alun-alun utara Surakarta. Pengaruh tingkat kepentingan elemen dari ruang terbuka publik berbeda-beda tergantung seting dan karakter dari ruang terbuka itu sendiri.Kata Kunci: Persepsi, Ruang terbuka publik, Multidimensional Scaling